Would Shared Health Visitor and Emergency Department Records Improve Recognition of Child Maltreatment within the Emergency Department? A Prospective Multicentre Study. (7th January 2021) - Nuttall, Diane; Rea, David; Bennett, C. Verity; Hollén, Linda; Mullen, Stephen; Maguire, Sabine; Emond, Alan; Kemp, Alison; Deave, Toity
Abstract : Burns are common causes of paediatric emergency care attendance; approximately ten per cent result from maltreatment. Following emergency department (ED) attendance with a burn by 232 under five‐year‐olds, 11 risk factors for maltreatment were collected via health visitor (HV) telephone surveys. Three of these risk factors (domestic violence, social care involvement and developmental impairment) were also available in ED records, and information collected was compared between the two. Non‐parametric Fisher's exact tests were applied. Fifty‐nine per cent of children lived in families with risk factors for maltreatment. Prominent risk factors known by HVs included: prior injuries ( n = 55, 23.7%), carer/parent mental health problems ( n = 48, 20.7%), domestic violence ( n = 47, 20.3%) and social care involvement ( n = 45, 19.4%). A total of 158 cases had complete data for all 11 risk factors: 49 (31.0%) lived in households with one factor, 22 (13.9%) with two factors and 27 (17.1%) with three or more risk factors. In cases where HVs recorded the following risk factors as present, EDs recorded five of 47 (10.6%) for domestic violence, ten of 45 (22.2%) with social care involvement and four of 23 (17.4%) with developmental impairment. Many risk factors that were known to HVs were not identified by EDs staff despite being part of a standardised proforma. Maltreatment risk assessment could be improved if EDs staff had access to HV information. Key Practitioner Messages: Fifty‐nine per cent of pre‐school children who attended an ED with a burn live in a family with one or more maltreatment risk factors, as identified by HV records. ED staff should be able to access a child's HV record electronically at the time of presentation, to identify known maltreatment risk factors. The lack of integration of community and acute setting health records is a barrier to comprehensive assessment and treatment decisions for children in EDs, especially in relation to safeguarding risks.